Follicle Center Lymphoma (FCL) of the Lower Female Genital Tract (LFGT): A Novel Variant of Primary Cutaneous Follicle Center Lymphoma (PCFCL). (1st March 2023) - Saksena, Annapurna; Jain, Ashish; Pack, Svetlana D.; Kim, Jung; Lee, Ina; Tyagi, Manoj; Xi, Liqiang; Pittaluga, Stefania; Raffeld, Mark; Jaffe, Elaine S.
Abstract : Primary cutaneous follicle center lymphoma has been distinguished from nodal follicular lymphoma (FL) based on genomic and clinical features. The nature of other extranodal FLs is not well defined. We report 15 cases of follicle center lymphoma involving the lower female genital tract. Cases were evaluated using an immunohistochemical panel for B-cell lymphoma, B-cell clonality, fluorescence in situ hybridization for BCL2 gene rearrangement, and next-generation sequencing. All patients had localized disease with no evidence of bone marrow involvement. Most cases (12/15, 80%) had a follicular pattern, at least focally. Large centrocytes were a prominent feature leading to concern for diffuse large B-cell lymphoma by referring pathologists. Neoplastic cells were positive for CD20 and BCL-6, while BCL-2 was positive in 2/15 (13%) cases. Fluorescence in situ hybridization for BCL2 gene rearrangement was negative in 10/11 (91%) cases. Next-generation sequencing performed in 10 cases revealed TNFRSF14 as the most frequently mutated gene in 6/10 (60%) cases. No case had CREBBP or KMT2D mutations as seen in nodal FL. None of the patients had progressive disease with durable complete remission achieved in 10/12 (83%) cases. The median follow-up period was 7.8 years (range: 0.2 to 20.5 y) with a 5-year overall survival of 100%. We conclude that follicle center lymphoma of the lower female genital tract is a novel variant of primary cutaneous follicle center lymphoma. Despite a frequent component of large cells, it is characterized by localized disease and low risk for dissemination. Awareness and recognition are important to distinguish these lesions from aggressive B-cell lymphomas.